2022
DOI: 10.3390/metabo12101003
|View full text |Cite
|
Sign up to set email alerts
|

Different Types of Non-Starch Polysaccharides Alter the Growth, Intestinal Flora and Serum Metabolite Profile of Grass Carp, Ctenopharyngodon idella

Abstract: Dietary non-starch polysaccharides (NSPs) broadly influence fish intestinal flora and physiological metabolism, but limited information is available on grass carp (Ctenopharyngodon idella). This study investigated the effects of different types of NSPs on the growth, nutrient metabolism status, gut microbiota, and serum metabolome of grass carp. Fish were fed with diets containing 4.4% insoluble NSPs (INSP), 9.24% soluble NSPs (SNSP), 13.64% NSPs (4.4% INSP + 9.24% SNSP, NSP) and non NSPs (FM), respectively, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 86 publications
0
0
0
Order By: Relevance
“…Insoluble ASP was superior to water-soluble WSP and CMP in increasing the richness and diversity of intestinal microorganisms. It has also been found that insoluble dietary fiber (IDF) is better than soluble dietary fiber (SDF) in alleviating colitis in mice by regulating gut microbiota [33] , and the addition of dietary insoluble polysaccharides can establish a health microbial community, which is conducive to intestinal health [34] . In this study, ASP and its modified product CMP showed stronger effects of promoting the proliferation of probiotics and inhibiting the growth of harmful bacteria than that of WSP.…”
Section: Discussionmentioning
confidence: 99%
“…Insoluble ASP was superior to water-soluble WSP and CMP in increasing the richness and diversity of intestinal microorganisms. It has also been found that insoluble dietary fiber (IDF) is better than soluble dietary fiber (SDF) in alleviating colitis in mice by regulating gut microbiota [33] , and the addition of dietary insoluble polysaccharides can establish a health microbial community, which is conducive to intestinal health [34] . In this study, ASP and its modified product CMP showed stronger effects of promoting the proliferation of probiotics and inhibiting the growth of harmful bacteria than that of WSP.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria DNA was extracted by a commercial kit using the SDS method (Magen, Guangzhou, China), following a quality and purity test. Subsequently, the DNA samples were amplified and purified according to the formulation of Liu et al [22], followed by library construction and sequencing of the cDNA. Sequencing work was carried out by Hiseq2500 PE250 platform (Illumina, San Diego, CA, USA), and sequencing data analysis work was carried out by Novogene Co., Ltd. (Beijing, China).…”
Section: Microbiome Analysismentioning
confidence: 99%